The impact of the interaction between BDNF rs7103411 gene polymorphism and social activities on mild cognitive impairment in community-dwelling elderly adults - Tan, Zhenkun; Ping, Junjiao; Zhang, Ying; Kong, Chuijia; Luo, Jiali; Liu, Xinxia (Frontiers in Psychiatry, 2025)
ObjectiveTo investigate the correlation between BDNF gene polymorphism, BDNF levels, and susceptibility to mild cognitive impairment (MCI).MethodsIn this study, we investigated 107 elderly adults individuals from a community in Zhongshan, Guangdong Province, with an average age of 73.17 ± 7.081 years. The participants included 52 patients with Mild Cognitive Impairment due to Alzheimer’s Disease and 55 cognitively normal elderly adults control subjects. The two groups were matched based on gender, age, and education level. We assessed their cognitive functions and analyzed their genotypes and serum BDNF levels. Analysis of covariance (ANCOVA) was used to evaluate the differences in serum BDNF levels between the MCI group and the control group. Multivariate linear regression was utilized to analyze the association between BDNF levels and susceptibility to MCI, as well as cognitive functions. Multivariate logistic regression was employed to investigate the association between BDNF gene polymorphisms and the risk of developing MCI, along with their interactions.ResultsThe ANCOVA analysis indicated that there was no significant difference in serum BDNF levels between the MCI group and the control group (P > 0.05). Correlation analysis revealed a negative correlation between Mini-Mental Status Examination (MMSE) total scores and MCI (r = -0.461, P = 0.001), with significant correlations observed in orientation (r = -0.420, P = 0.002). Multiple linear regression analysis showed that specific polymorphisms, including rs7103411 (CT+TT vs. CC), rs6265 (CT and CT+TT vs. CC), rs11030104 (AG and AG+GG vs. AA), and rs988748 (CG+CC vs. GG), were significantly associated with decreased serum BDNF levels (P < 0.05). Multivariate logistic regression showed that rs7103411 polymorphism was associated with susceptibility to MCI; individuals with the CT or CC genotype had a 0.370 times lower risk of developing MCI compared to those with the TT genotype (OR = 0.370, 95% CI: 0.141-0.970, P = 0.043). A significant interaction was found between rs7103411 and social activity, which influenced the risk of developing MCI. Specifically, individuals with the CT or TT genotype of rs7103411 who engaged in social activities had a significantly lower risk of developing MCI (OR = 0.32, 95% CI: 0.117-0.878, P = 0.027).ConclusionThis study indicates that BDNF rs7103411、rs6265、rs11030104 and rs988748 are associated with decreased serum BDNF levels in MCI patients. Individuals carrying the TT genotype in the BDNF rs7103411 gene are associated with an increased susceptibility to MCI. Individuals with the rs7103411 CT or TT genotype who participated in social activities showed a significantly reduced risk of developing MCI, suggesting that the interaction between the BDNF rs7103411 genotype and social activity can help reduce the risk of MCI.